Language skills assessment: electronic test application with second language learners - Figueiredo, Sandra (2018)
Second language learners are students at risk in what concerns developing literacy abilities, which may determine their academic performance in general. The purpose of the study was to develop a reliable electronic instrument to assess verbal behaviours, regarding the phonological awareness and specific language skills of second language (SL) learners. The general results gathered from the participants’ achievement reveal that the older learners present higher competence than younger ones, exhibiting more structure and less intereference at the phonological level. In this paper we are adressing specific data related to perception and production skills, regarding the reading and spelling skills (assessed in the test n.º4 of the battery) in second language context. The age of acquisition and the type of the first linguistic system could be the main factors influencing the verbal repertoires and determining the abilities regarding articulation and perception of sounds in foreign phonetic system. The general tests battery is presented as an important diagnostic tool applied to educative contex in a multicultural society. Considering this, the tests battery developed in this research is a contribute for Education, in that it holds as an important instrument of diagnostic evaluation, and simultaneously as an intervention program in teaching and learning, especially directed at students who are initiating the learning/acquisition process of Portuguese as a SL, for it may provide indicators to facilitate the process of attribution of proficiency levels by the teacher/educator, according to students’ performance. The test configuration is based on the principle of organization by task level which garantees precision on sound stimuli hearing, conditioned writing tasks, time counting in each task (reaction time recorded), a consistent data basis and immediate presentation of score at the end of the screening test.